Mechanism of carbon nanotube growth in expanded graphite via catalytic pyrolysis reaction using carbores P as a carbon source - Wang, Yilong; Zhang, Wenli; Chen, Yuejun; Zeng, Xiongfeng; Huang, Jiankun; Wei, Hengyong; Tu, Junbo (Frontiers in Chemistry, 2023)
Carbon nanotubes in situ growth in expanded graphite (EG) were successfully prepared via catalytic pyrolysis reaction using carbores P as carbon source and Co(NO3)3•6H2O as catalyst. The results of XRD, SEM and EDS indicated the carbon nanotubes could generate in EG with the presence of carbores P as carbon source and cobalt nitrate as catalyst. More interesting, the growth mechanism of carbon nanotubes could be concluded by the analysis results of DTA-TG-MS and XPS. It was that the pyrolysis products of carbores P were mainly hydrocarbon gas such as CH4 gas, which react with Co(NO3)3•6H2O catalyst to reduces CoOx to Co particles, then the C atom form pyrolysis contacted with the catalyst Co particles, after continuous solid dissolution and precipitation, carbon nanotubes generated in EG at last.